The Stages of Organizing Social Cooperation Between Educational Institutions and Enterprises in Directing Guards to Professions (Eurasian Scientific Herald, 2022)
Attracting cooperation in the creation of the content of vocational education is achieved by analyzing the labor market and its main tasks, the object of the labor market analysis and the analysis of the needs for professional knowledge, skills and qualifications. This article shows that the educational process, which is organized within the framework of social cooperation between educational institutions and enterprises, is carried out within a number of interconnected activities.